2014
DOI: 10.3389/fimmu.2014.00331
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Resident Memory CD4 T Cells in Protection and Immunopathology

Abstract: Tissue-resident memory T cells (TRM) comprise a newly defined subset, which comprises a major component of lymphocyte populations in diverse peripheral tissue sites, including mucosal tissues, barrier surfaces, and in other non-lymphoid and lymphoid sites in humans and mice. Many studies have focused on the role of CD8 TRM in protection; however, there is now accumulating evidence that CD4 TRM predominate in tissue sites, and are integral for in situ protective immunity, particularly in mucosal sites. New evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
178
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(188 citation statements)
references
References 125 publications
6
178
0
4
Order By: Relevance
“…Similar as CD4 + T RM clusters in the skin and vagina, clusters of lung CD4 + T RM have been identified after influenza virus infection, 170 suggesting a common mechanism underlying CD4 + T RM differentiation and/or maintenance. In contrast to lung CD8 + T RM cells, one report has suggested that mouse lung CD4 + T RM is TGF-β-independent, consistent with a CD103 − phenotype.…”
Section: Cd4+ Trm Cellsmentioning
confidence: 83%
See 2 more Smart Citations
“…Similar as CD4 + T RM clusters in the skin and vagina, clusters of lung CD4 + T RM have been identified after influenza virus infection, 170 suggesting a common mechanism underlying CD4 + T RM differentiation and/or maintenance. In contrast to lung CD8 + T RM cells, one report has suggested that mouse lung CD4 + T RM is TGF-β-independent, consistent with a CD103 − phenotype.…”
Section: Cd4+ Trm Cellsmentioning
confidence: 83%
“…CD4 + T RM cells represent a critical adaptive component of local immunity. 170 We will use the last section to summarize the recent findings about CD4 + T RM cells in various tissues. We will not include Foxp3 + regulatory T cells in our discussion as recent reviews have covered the related findings.…”
Section: Cd4+ Trm Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that IAV-specific memory CD4 T cells contribute to develop protective immune responses against respiratory viral infection (42). On the one hand, typical secondary recall responses to antigens by memory CD4 T cells in the lung participate in direct viral clearance (43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mouse models of infection have used T cell adoptive transfers [25, 26], parabiosis (surgical conjoining of two mice to create shared circulation) [22], and intravenous infusion of fluorescent antibodies to label T cells in circulation versus those within tissues [27] to distinguish between these possibilities. In mice, tissue T cells comprise both circulating and tissue resident memory T cells (TRM), with TRM found in multiple sites including lungs, intestines, skin, vaginal mucosa, liver, intestines, and to lesser extents in lymph nodes [2631]. These non-migratory TRM can be generated from site-specific infection in skin, lungs, and vaginal mucosa, and are specifically retained within these sites [26, 3235].…”
Section: Introductionmentioning
confidence: 99%